Scytinopogon cryptomerioides (Hydnodontaceae), a new species from Taiwan - Lin, Wan-Rou; Wang, Pi-Han; Hsieh, Sung-Yuan (Phytotaxa, 2022)
Scytinopogon cryptomerioides (Trechisporales, Basidiomycota) is described as a new species collected from Cryptomeria japonica plantations in Taiwan. This new species is characterized by a white basidiome with dichotomous and flattened branches, clamped hypha, ampullate septa, clavate basidia with four sterigmata, and colorless, ellipsoid, echinulate or verrucose spores with acute warts or spines. Based on the phylogeny constructed from a combined dataset of ITS-nrLSU sequences, S. cryptomerioides nested within the Trechispora clade, sister to Trechispora copiosa.